Geloofsonderskeiding in die Oostelike Sinode van die NG Kerk tydens die besluitnemingsprosesse oor die wysiging van Artikel 1 van die Kerkorde - Louwrens, Carl; Hendriks, Jurgens (Stellenbosch Theological Journal, 2018)
Faith discernment in the Eastern Synod of the DR Church during the resolution processes on the amendment of Article 1 of the Church Order During 2014, the DRC came to a point where they had to decide whether they would amend their confessional base to include the Belhar Confession as part of their official doctrine. The General Synod suggested amending Article 1 of the Church Order in order to expand the confessional base. An amendment of the Confession is possible after it has been approved by a two-thirds majority of each synod and two-thirds of all the church councils. In both cases it needs a two-thirds majority. 58% of the congregations in the Eastern Synod voted against the amendment of Article 1 in September 2014. In October 2014 the Eastern Synod voted in favour of the amendment of Article 1 with a majority of 73%. This article reflects on why the result of the spiritual discernment process was so different between the synod and the church councils of the Eastern Synod.